(untitled) (World Bulletin of Public Health, 2026)
This topic provides a comprehensive overview of the interpretation of cytological examination results using the Bethesda System. It highlights the importance of standardized reporting in cytology, particularly in cervical cancer screening programs. The annotation explains how the system classifies cellular findings into categories such as normal, atypical, lowgrade, and high-grade lesions, helping healthcare professionals identify early pathological changes